Displays of parent suitability in adoption assessment reports. (8th July 2016) - Lind, Judith; Lindgren, Cecilia
Abstract: Through adoption, the state actively contributes to creating families. It therefore also assumes the role of guarantor of the child's best interests in the adoption process, which entails assessing the suitability of presumptive adoptive parents. In the present paper, we use the concluding sections of assessment reports on applicants for intercountry adoption in Sweden to answer the following question: what must be said about an individual or a couple in order for her/them to be seen as a suitable adoptive parent? We thus assume that report conclusions serve to display parent suitability to their audiences. The assessment aligns with Swedish national adoption guidelines, and the study shows how the assessment handbook comes to serve as a catalogue of arguments that not only define good parenthood but also outline a way of life that is suitable for parenthood. The analysis illustrates how valid arguments for granting consent to adopt refer to three layers of suitability. They include not only the applicants' insights into and knowledge about adoption in particular and children in general but also their conventional and orderly life, i.e. a life free from distractions that could hinder a wholehearted focus on children and family life.